2017
DOI: 10.1088/1361-6579/aa68ce
|View full text |Cite
|
Sign up to set email alerts
|

Detecting colorectal cancer using electrical impedance spectroscopy: anex vivofeasibility study

Abstract: This feasibility study demonstrates that impedance spectra changes in colorectal cancer tissue are detectable and may be statistically significant, suggesting that EIS has the potential to be the core technology in a novel non-invasive point of care test for detecting colorectal cancer. These results warrant further development by increasing the size of the study with a device specifically designed for colorectal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…Previous research suggested that GNPs has the potential as a contrast agent for bioimpedance measurements [15] and it is possible to detect cancer cells based on the impedance increase [16]. However, the addition of GNPs to decrease impedance in cancer cells would limit the ability to distinguish between GNPs and cancer cells.…”
Section: A Gnps As Contrast Agentsmentioning
confidence: 99%
“…Previous research suggested that GNPs has the potential as a contrast agent for bioimpedance measurements [15] and it is possible to detect cancer cells based on the impedance increase [16]. However, the addition of GNPs to decrease impedance in cancer cells would limit the ability to distinguish between GNPs and cancer cells.…”
Section: A Gnps As Contrast Agentsmentioning
confidence: 99%
“…It has a wide range of applications that can help in clinical status monitoring and diagnosis of diseases [2]. Example applications include human-machine interfaces [3], lung function monitoring [4], drug-screening [5], biosensing [6], and cancer detection [7].…”
Section: Introductionmentioning
confidence: 99%
“…As an electrochemical analysis technique, EIS has historically been used industrially for monitoring corrosion (Angelini et al 2006) and battery efficiency (Din et al 2016), while its use for medical applications is less well established (Pathiraja et al 2017). EIS relies on the physical and chemical properties of molecules to alter the transmission of electrical current (Carminati and Li 2017).…”
Section: Introductionmentioning
confidence: 99%